South–South Cooperation in Southeast Asia: From Bandung and Solidarity to Norms and Rivalry. Issue 2 (August 2019) - Engel, Susan
This article demonstrates how South–South Cooperation (SSC), as it is now constituted in Southeast Asia, is little more than a liberal norm retaining only echoes of its origins in the 1955 Bandung Conference that first created SSC based on solidarity, common interests, and sovereignty. Southeast Asia is a useful case study of SSC's evolution, as its states have been major players over the decades – with Indonesia proposing the Bandung Conference, Malaysia playing a key role in the 1980s, and Indonesia again at the forefront of the region from the first years of the new century onwards. Thailand and Singapore also have notable SSC programmes. However, the practices of SSC in the region show that it has become a liberal norm based on one key instrument – technical cooperation programmes. The process of SSC norm internalisation has occurred through a complex webbing of the interests and ideas of Southeast Asia's states, regional dynamics, and Northern donor interests.